2019
DOI: 10.1038/s41396-018-0320-9
|View full text |Cite
|
Sign up to set email alerts
|

Light limitation increases multidimensional trait evenness in phytoplankton populations

Abstract: Individual-level variation arising from responses to environmental gradients influences population and community dynamics. How such responses empirically relate to the mechanisms that govern species coexistence is, however, poorly understood. Previous results from lake phytoplankton communities suggested that the evenness of organismal traits in multiple dimensions increases with resource limitation, possibly due to resource partitioning at the individual level. Here we experimentally tested the emergence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 33 publications
(40 reference statements)
4
32
0
Order By: Relevance
“…However, the absence of non‐additive effects in their study might be due to the use of one single leaf litter species, which decreases the opportunities for intraspecific niche partitioning. Our results built upon this previous knowledge (the differences in consumption rates detected so far among conspecific individuals do not automatically imply complementary resource use) and allowed us to experimentally demonstrate for the first time that intraspecific trait variation matters for small‐scale niche partitioning in soil fauna, as it was already shown for primary producers in different systems (Fontana, Thomas, Reyes, & Pomati, ; He et al, ), and has consequences for fundamental ecosystem processes.…”
Section: Discussionsupporting
confidence: 72%
“…However, the absence of non‐additive effects in their study might be due to the use of one single leaf litter species, which decreases the opportunities for intraspecific niche partitioning. Our results built upon this previous knowledge (the differences in consumption rates detected so far among conspecific individuals do not automatically imply complementary resource use) and allowed us to experimentally demonstrate for the first time that intraspecific trait variation matters for small‐scale niche partitioning in soil fauna, as it was already shown for primary producers in different systems (Fontana, Thomas, Reyes, & Pomati, ; He et al, ), and has consequences for fundamental ecosystem processes.…”
Section: Discussionsupporting
confidence: 72%
“…We use chlorophyll-a measurements in phytoplankton monocultures as experimental support for our theoretical findings (Section 3). Our chlorophyll measurements were derived from experimental data described in detail in Fontana et al (2019), which we summarise briefly here. Kirchneriella subcapitata (a eukaryotic green alga) and Microcystis aeruginosa (a prokaryotic cyanobacterium) were grown in monocultures under several different, but constant, light intensities and a constant temperature of 20 • C. All cultures were subjected to the same light-dark cycle, with 14 hours light and 10 hours darkness, and measurements were taken during the light period.…”
Section: Phytoplankton Chlorophyll Content Under Different Light Intementioning
confidence: 99%
“…Additionally, for each replicate (species and light intensity), there was an additional monoculture of the other species in a separate container, that was shaded by the first (no mixing). The mixed cultures described in Fontana et al (2019) are not considered here. The data were collected using a scanning flow cytometer as described in Fontana et al (2019), from which we only analyse live cells that were identified through clustering and a trained random forest classification algorithm (Thomas et al, 2018).…”
Section: Phytoplankton Chlorophyll Content Under Different Light Intementioning
confidence: 99%
See 2 more Smart Citations